Case Study: Participatory Ergonomics in Road Construction and an Occupational Perspective of Health. (September 2016) - Pazell, Sara; Burgess-Limerick, Robin; Horberry, Tim
Road construction comprises high-risk work activity including risks for collision, musculoskeletal disorder, and slips, trips and falls. A participatory ergonomics project was hosted after compelling field observations were made. A manual task involving roll-out of multi-laminate tape was redesigned with the fabrication of a customized trolley. A human-centered design process was engaged (The Design for Operability and Maintainability Technique) and the project outcomes were reviewed according to an Occupational Perspective of Health, a spectrum of safety through to productivity (or "doing – being – becoming – belonging"). Critical success factors of the project are described, also, to inform activity that may sustain a participatory ergonomics and human-centered design practice.